2019
DOI: 10.3389/fmicb.2019.00588
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Communities of Transgenic Poplar Were Determined by the Environment and Niche Rather Than by Transgenic Events

Abstract: Microbial communities associated with plants represent key determinants of plant health, survival, and growth. However, a good understanding of the structural composition of the bacterial and fungal microbiome present in different plant tissues and growing environments, especially in transgenic woody plants, is required. In the present study, we hypothesized that environmental conditions, ecological niches, and transgenic events could influence the community structure of plant-associated microorganisms (bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 84 publications
3
15
0
Order By: Relevance
“…The highest evenness of bacterial communities was found in the stem among plant parts. It should be noticed that there was no significant difference in bacterial diversity between stems and roots, while many studies have determined that bacterial diversity was highest in roots (Santana et al, 2016;Wang et al, 2019). The variation of endophytic bacterial communities in different compartments was primarily driven by tissue-specific filtering mechanisms within the host (Bonito et al, 2014;Chao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The highest evenness of bacterial communities was found in the stem among plant parts. It should be noticed that there was no significant difference in bacterial diversity between stems and roots, while many studies have determined that bacterial diversity was highest in roots (Santana et al, 2016;Wang et al, 2019). The variation of endophytic bacterial communities in different compartments was primarily driven by tissue-specific filtering mechanisms within the host (Bonito et al, 2014;Chao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also pointed out that variations of the relative abundances of Acidobacteria, Actinobacteria, and Bacteroidetes in soil microbial communities are mainly driven by soil pH, which further affect the overall structural variability of bacterial communities (Lauber et al, 2019). According to the findings of a recent study that investigated the bacterial communities in poplar roots, pH has a significant influence on the genotypes of both bacterial and fungal communities, as well as their colonization and distribution in plant roots and stems (Wang et al., 2019). As a result, microbes in root‐zone soil and intershrub bulk soil are mainly influenced by pH and NH 4 + ‐N.…”
Section: Discussionmentioning
confidence: 99%
“…This 91 phenomenon suggests that soil type is an important driver of microbial community composition in the 92 rhizosphere (33, 34). Findings from previous studies have also indicated that core bacterial 93 microbiomes closely associated with host plants dominate the degree of variability of the entire 94 bacterial community across different niches (23, 35). As far as rhizocompartments are concerned as 95 special micro-ecosystems, the relative differential variations of bacterial communities driven by 96 various soil factors in roots, rhizosphere soil, and non-rhizosphere soil can be used to reflect the 97 intensity of the "rhizosphere effect", and characterize the degree of interactions between plants and 98 soil.…”
Section: Introduction 44mentioning
confidence: 95%